Pengembangan Historiografis sebagai Media Pembelajaran Sejarah SMA Materi Peninggalan Praaksara di Kabupaten Lima Puluh Kota Sumatera Barat - Hutrisni, Mardhyyah; Hastuti, Hera (Jurnal Kronologi, 2025)
This reserch began with the problems encounteredin the field, namely the absence of history kearning media available at SMAN 1 Kecamatan Guguak regarding local history of prehistori cheritage in Lima Puluh Kota Regency and the still minimaluse of IT-based media inhistory learningat SMAN 1 Kecematan Guguak. This research aims to develop and analyze the feasibility, as well as evaluate the level of practicality and effevctiveness of historiographic-based history learning media containing local history. The local history in this study is prehistoric heritage in Limia Puluh Kota Regency. The type of research used is development esearch or Research and Development (R&D) using the ADDIE model. The subjects of this study were 32 students of class X of SMAN 1 Kecamatan Guguak. The results of the study were obtained through several stages, namely: 1) analysis of needs related to teachers, curriculum and students; 2) design of learning media using Canva; 3) the results of the material feasibility test showed an average value of 3,62 and the results of the learning media feasibility test showed an average value of 3,61, both of which are included in the very feasible category; 4) the implementation stage is seen from the results of the practicality test with an average score of 3,72 from teachers and 3,43 from students, categorized as very practical; 5) the evaluation stage can be seen from the effectiveness test by analyzing interview responses with teachers, wihic shows historiography as an effective learning medium used in the history learning process.